Single commercially available ic-based electronically controllable voltage-mode first-order multifunction filter with complete standard functions and low output impedance - Jaikla, Winai; Buakhong, Unchittha; Siripongdee, Surapong; Khateb, Fabian; Sotner, Roman; Silapan, Phamorn; Suwanjan, Peerawut; Chaichana, Amornchai (My University, 2021)
This paper presents the design of a voltage-mode three-input single-output multifunction first-order filter employing commercially available LT1228 IC for easy verification of the proposed circuit by laboratory measurements. The proposed filter is very simple, consisting of a single LT1228 as an active device with two resistors and one capacitor. The output voltage node is low impedance, resulting in an easy cascade-ability with other voltage-mode configurations. The proposed filter provides four filter responses: low-pass filter (LP), high-pass filter (HP), inverting all-pass filter (AP−), and non-inverting all-pass filter (AP+) in the same circuit configuration. The selection of output filter responses can be conducted without additional inverting or double gains, which is easy to be controlled by the digital method. The control of pole frequency and phase response can be conducted electronically through the bias current (IB). The matching condition during tuning the phase response with constant voltage gain is not required. Moreover, the pass-band voltage gain of the LP and HP functions can be controlled by adjusting the value of resistors without affecting the pole frequency and phase response. Additionally, the phase responses of the AP filters can be selected as both lagging or leading phase responses. The parasitic effects on the filtering performances were also analyzed and studied. The performances of the proposed filter were simulated and experimented with a ±5 V voltage supply. For the AP+ experimental result, the leading phase response for 1 kHz to 1 MHz frequency changed from 180 to 0 degrees. For the AP− experimental result, the lagging phase response for 1 kHz to 1 MHz frequency changed from 0 to −180 degrees. The design of the quadrature oscillator based on the proposed first-order filter is also included as an application example.
Keywords: Active building block; Electronic control; First-order circuit; LT1228; Multifunction filter; Phase shifted circuit; Voltage-mode